Possible effects of melatonin on the kidney of hyperthyroid rats - Oner, J; Ozan, E; Kukner, A; Oner, H (Sciendo, 2002)
The aim of this study was to investigate structural changes that occurr in the kidney of rats with hyperthyroidism and the effect of melatonin on these changes. The rats were divided into 3 groups; group I was designated as the control, group II was injected daily with 3,3,5-triiodo-L-thyronine (T-3) and group III was injected daily with T-3+melatonin. After 40 days, tissue specimens of kidney were removed and examined by light and electron microscopy. In the proximal tubule of the T-3 injected group, basement membrane thickening, microvillus irregularity and evidence of basal folding were observed. In the glomerule, basal lamina thickening, irregularity of pedicels and somewhere an increase of mesangium were recorded. Moreover, in the melatonin injected group, the findings were similar to the T-3 injected group. In conclusion, it was observed that hyperthyroidism caused structural changes in the kidney and melatonin had no important effects on these changes.
Keywords: hyperthyroidism; kidney; melatonin; microscopy